1999
DOI: 10.1210/endo.140.1.6444
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Priming Is Essential for the Full Expression of the Positive Feedback Effect of Estradiol in Inducing the Preovulatory Gonadotropin-Releasing Hormone Surge in the Ewe

Abstract: The luteal phase elevation in circulating progesterone (P) powerfully inhibits GnRH and, consequently, LH release, thereby preventing premature preovulatory LH surges in the ewe. Whether luteal phase P modulates the response of the GnRH system to the positive feedback effect of estradiol is unknown. To investigate this possibility, two experiments were conducted during the anestrous season using an artificial model of the follicular phase in ovariectomized ewes bearing 10-mm s.c. 17beta-estradiol SILASTIC bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 39 publications
2
34
0
1
Order By: Relevance
“…A fourth group (NC; n = 7) was pretreated with progesterone, but did not receive an estradiol increment. Based on previous reports [1, 13], GnRH surges were expected in the –P (normal amplitude) and +P (enhanced amplitude) groups but were not expected in the PB (activation of the surge blocked) and NC (no stimulatory estradiol signal) groups. The experimental protocol is summarized in figure 1.…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…A fourth group (NC; n = 7) was pretreated with progesterone, but did not receive an estradiol increment. Based on previous reports [1, 13], GnRH surges were expected in the –P (normal amplitude) and +P (enhanced amplitude) groups but were not expected in the PB (activation of the surge blocked) and NC (no stimulatory estradiol signal) groups. The experimental protocol is summarized in figure 1.…”
Section: Methodsmentioning
confidence: 76%
“…Therefore, the onset of the LH surge was used as a marker of the start of the GnRH surge. Treating ewes with luteal phase concentrations of progesterone prior to the stimulation of a GnRH/LH surge with estradiol enhances the amplitude and delays the onset of the GnRH surge [13, 36]. We used the delay of the LH surge onset to indicate that the stimulatory progesterone treatment was effective.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, hormonal assay in blood samples clearly indicated that progesterone had completely cleared before male introduction. Secondly, the differences found in our study might be due to exposure of the gonadotrophin-releasing hormone (GnRH) system to powerful inhibitory effect of progesterone (Caraty & Skinner 1999). According to this hypothesis, following CIDR removal, the response of the hypothalamuspituitary axis to the stimulatory signals of males might be delayed, resulting in a slow follicular growth rate and a late LH surge.…”
Section: Discussionmentioning
confidence: 75%